2008
DOI: 10.1583/08-2443.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stent Design and Atherosclerotic Plaque Composition on Arterial Wall Biomechanics

Abstract: ¤ ¤Purpose: To examine the solid mechanical effects of varying stent design and atherosclerotic plaque stiffness on the biomechanical environment induced in a diseased artery wall model. Methods: Computational modeling techniques were employed to investigate the final radius of the lumen and artery wall stresses after stent implantation. Two stent designs were studied (one stiff and one less stiff). The stenotic artery was modeled as an axisymmetrical diseased vessel with a 20% stenosis by diameter. The materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…One of the more obvious mechanisms is the development of atherosclerotic plaques [33]. Atherosclerosis in the coronary arteries (and at other sites) has been consistently associated with increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more obvious mechanisms is the development of atherosclerotic plaques [33]. Atherosclerosis in the coronary arteries (and at other sites) has been consistently associated with increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Although the bending cycle simulated here is not predicted to cause fatigue failure of the stent (FOS greater than one for all integration points), this is for an idealised artery and a relatively short stent. A calcified or eccentric plaque [32], a longer lesion (and stent) or a more irregular vessel geometry would be amongst the factors that could reduce the factor of safety and lead to stent fatigue fracture.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,15,18,23,33 However, the only numerical studies conducted on stent mis-sizing were found to be on balloon-expandable stents deployed in straight cylindrical models of healthy 3,18 or calcified coronary arteries. 37 Due to the significant differences in their deployment procedures, the results from these studies could not be adopted for self-expandable Nitinol stents. Thus, the aim of the present study was to quantify the biomechanical effects of Nitinol stent oversizing using numerical models of non-calcified popliteal arteries obtained from patients undergoing endovascular revascularization.…”
Section: Introductionmentioning
confidence: 99%